The Influence of Motivation and Work Stress on the Organizational Commitment of Civil Servants in the Population and Civil Registration Office of Pontianak City - Gea, Zeldi; Ahmadia, Eru (SAINTIS Publishing, 2025)
This study examines the impact of motivation and work stress on the organizational commitment of civil servants at the Pontianak City Population and Civil Registration Office. The study highlights the importance of human resource management in achieving organizational goals, emphasizing motivation and stress as key factors influencing employee commitment. The study aims to analyze this relationship quantitatively using an associative approach. Data collection was carried out through questionnaires distributed to 49 respondents, supplemented by secondary data related to violations and employee performance values. Sampling used saturated sampling technique. This study used multiple linear regression analysis, supported by classical assumption tests such as validity, reliability, normality, linearity, and multicollinearity tests. The results showed a positive relationship between motivation and organizational commitment, as well as between work stress and organizational commitment. Simultaneous testing showed that both variables significantly influenced organizational commitment. The R-square value of 20.6% indicates that other factors contributed 79.4% to organizational commitment. This study underlines the importance of addressing motivation and work stress to increase employee commitment, offering insights to improve organizational performance through strategic interventions